Estudo clínico randomizado e aberto para avaliação de eficácia e superioridade dos medicamentos EF028 aerossol, EF028 creme e Andolba® frente ao tratamento controle e comparativo de não inferioridade entre os medicamentos EF028 aerossol, EF028 creme e Andolba® para avaliação de eficácia na redução da sintomatologia dolorosa - Da Costa, Marcelo Cariola Corrêa; Carramão, Sílvia Silva; Pinto, Patrícia Camarano [UNESP]; Milan, Ana Lúcia Koff; Pannuti, Estela Maia Bellini [UNESP] (My University, 2010)
Aim: This study aimed to evaluate the efficacy of a new topical drug (EF028) in two separate presentations (aerosol and cream) in a comparative way with the already registered medication, Andolba® (benzocaine, benzoxiquina chloride benzeconio, menthol) and the negative control (hygiene), in the analgesic efficacy after episiotomy wound, reducing the requirement for systemic medication. Methods: 60 patients were voluntary post normal vaginal childbirth with episiotomy, were divided into four groups to comparatively assess the action of the product EF028 (cream and aerosol), Andolba® and soap, the efficacy of decreasing painful symptoms from daily use for 2 times a day for seven days. Clinical assessments and subjective pain occurred daily until the third postoperative day and on the 7th postoperative day. Results: The results showed that the drugs promoted a reduction of painful symptoms and there was no statistically significant difference (p <0.05) between presentations of drug EF028 (cream and aerosol) and Andolba® and the three products were significantly higher (p <0.05) to the control. Conclusions: The evaluated drugs EF028 aerosol, EF028 cream and Andolba® had similar efficacy in relieving the painful symptoms of the perineal region in postoperative episiotomy can be considered as indication for postoperative episiotomies. © Copyright Moreira Jr. Editora.
A randomized, open-label evaluation of efficacy and superiority of the medications aerosol EF028, cream EF028 and Andolba® front of the control treatment and comparative of non-inferiority between the medications aerosol EF028, cream EF028 and Andolba® to evaluate effectiveness in reducing symptoms painful of episiotomy postoperative in parturient with vaginal child-bearing
Keywords: Episiotomy; Local anesthesia; Normal childbirth; analgesic agent; andolba; benzocaine; benzocaine plus menthol; ef 028; menthol; unclassified drug; adult; analgesic activity; clinical trial; controlled clinical trial; controlled study; drug dosage form comparison; drug efficacy; drug screening; episiotomy; female; human; major clinical study; open study; pain assessment; postoperative pain; randomized controlled trial; treatment response; vaginal delivery